Novas interpretações das questões jurídicas sob a ótica do Capitalismo Humanista - Toledo, Armando Sérgio Prado de (2014)
The contemporary judge has in Federal Constitution the main text from which should draw the principles and rules that should apply in solving the cases that are presented to her or him on a day-to-day. However, it stands out for its importance, the principle of human dignity, to the extent that the capitalist society, based on the appropriation of wealth and exploitation of human labor, perceives as its main goal the true development of the human being. Accordingly, the magistrate should seek realize a fraternal right, harmonizing it to the right to social and economic development in light of a man exercising the plenitude of its rights and values. The judge is no longer seen as mere supporting role in implementing the law, the law enforcer, who performed only the subsumption of fact in the standard model designed by the pure positivism. Nowadays, the judge should work with legal precepts open and programmatic principles that shape an individual's life. Therefore, it is critical that the magistrate has ethically committed to the development of activities fomenting the dignity of the human person, though not losing sight of the the economic model adopted by the Brazilian state that is capitalist, and characterized therefore by free enterprise and ownership deprived of the means of production. It is quite evident that the traditional instruments of interpretation of legal norms, especially those contained in the Federal Constitution, from which one draws the guiding principles such a model of society, should be reviewed and attuned to the current time. The Humanist Capitalism, as a philosophical movement that reconciles the natural desire of man with the right of ownership in order to make his dreams come true by socialization of wealth, becomes an important instrument available to the magistrate for his ethical stand in carrying out his salutary functions to strengthening democracy